VET Data Report Germany 2016/2017 : facts and analyses accompanying the Federal report on vocational education and training - selected findings - Le Mouillour, Isabelle [Herausgeber]; Friedrich, Michael [Herausgeber] (Bundesinstitut für Berufsbildung, 2018)
"The development of the German vocational education and training system and more specifically of the dual system relies on regular data collection. Statistical analysis and surveys are continuously informing policy decisions and supporting practices. Traditional aspects of apprenticeship in terms of indicators on apprentices, companies or occupations are provided. Each year BIBB colleagues select a key topic by relevance to VET stakeholders in Germany: The 2016/2017 report delivers in-depth data on access and participation of refugees to vocational education and training in Germany. Exceptionally this report is based on two original data reports from the years 2016 and 2017. The Data Report of the Federal Institute for Vocational Education and Training (BIBB) is a selection of most relevant and actual data on the German Vocational Education and Training system addressing a wide range of VET stakeholders in English. By consulting the BIBB website (www.bibb.de/datenreport) interested colleagues have access to full statistical data and further sources." (Editor, BIBB-Doku)
Keywords: G 1.3 Aus- und Weiterbildungsmarkt; G 1.2.3.2 Anforderungen & Bedarfe; S 2.3 Berufsbildungspolitik; S 1.5.2 Berufliche Weiterbildung; S 1.3.1 Ausbildung im Dualen System; Berufsbildungsbericht; Berufsbildungsstatistik; Berufsbildungspolitik; Berufsausbildung; Flüchtling; Ausbildungsstellenmarkt; Fachkräftebedarf; Mismatch; Ausbildungsplatznachfrage; Weiterbildung